PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DALAM PENINGKATAN EFEKTIVITAS ORGANISASI PENDIDIKAN - Hermansyah; Sawiyah Siagian, Lailan; Noryani, Noryani; Mulyati; Dwiyono, Yudo (SISTEMA: Jurnal Pendidikan, 2024)
Transformational leadership emphasizes change and innovation to achieve organizational goals, which is crucial in the complex field of education. Such leaders inspire, motivate, and empower staff and students, enhancing educational effectiveness through gradual, systematic changes. This study uses a literature review to analyze the impact of transformational leadership on educational organization effectiveness. Findings show that transformational leadership is key in forming a strong, inclusive culture, fostering collaboration, and improving satisfaction and academic performance. The study indicates a positive correlation between transformational leadership and educational performance. Successful implementation requires strong interpersonal skills and organizational support. This research provides valuable insights into strategies for applying transformational leadership to boost educational organization effectiveness.   Keywords: Transformational leadership, organizational effectiveness